Burden of cervical cancer in Martinique, 2012–2021 - Houpert, Rémi; Sylvestre, Emmanuelle; Bouhnik, Anne-Déborah; Ben-Diane, Marc-Karim; Najioullah, Fatiha; Almont, Thierry; Boutant, Wendy; Macni, Jonathan; Mancini, Julien; Joachim, Clarisse; Veronique-Baudin, Jacqueline (Cancer epidemiology, 2025)
To provide an updated overview of the burden and temporal trends in incidence, mortality and survival of cervical cancer in a French Caribbean region between 2012 and 2021. This retrospective study included all cases of cervical cancer diagnosed and registered by the Martinique Population-Based Cancer Registry between 2012 and 2021. Data were recorded strictly according to international standards set by the International Agency for Research on Cancer, French and European Network of Cancer Registries. A descriptive epidemiological analysis and a survival analysis for invasive cases were performed. We calculated world age-standardized incidence and mortality rates, using the WHO standard world population. Overall survival, with a 95 % confidence interval, was calculated as the time from diagnosis to death from any cause. Patients were censored at the date of last follow-up or at the cut-off date of December 31, 2023. We used the Kaplan-Meier product limit method to estimate overall survival at 1, 3, 5 and 10 years. Over the study period, 1196 in situ tumors and 202 invasive cases were diagnosed. 45.0 % of women were aged 65 and over, and 67.3 % received chemotherapy and/or radiotherapy. Most invasive cases were diagnosed with locally advanced stage (43.1 %) and were squamous cell carcinomas (75.2 %). Trends in world age-standardized incidence and mortality rates were globally constant at 6 per 100,000 and 3 per 100,000 person-years, respectively. Overall survival at 5 years was 51.4 % (44.2 %; 58.1 %), and at 10 years, 41.8 % (33.8 %; 49.6 %). In this retrospective cohort study, data from a qualified cancer registry comprehensively described the burden of cervical cancer in a Caribbean region. These findings are essential for planning, monitoring, and evaluating the ongoing impact of the national vaccination, screening, and treatment measures required to drastically contribute to the elimination of cervical cancer in these particularly high-burden regions. [Display omitted] •202 invasive cases of cervical cancer were diagnosed between 2012 and 2021.•World age-standardized incidence and mortality rates were 5.9 and 2.6 per 100,000.•43.1 % were locally advanced (FIGO stage IIA-IIIC2) and 75.2 % was squamous carcinoma.•Overall survival at 5 years was 51.4 %, and at 10 years, 41.8 %.